A phenomenological inquiry of higher education institutions’ (HEIs) online experiences: listening to the voices of the stakeholders - Carag, Eduardo A. (Linguistics and Culture Review, 2021)
The capability of Higher Education Institutions (HEIs) presents instructional innovations to assist educational institutions in the cause of the paradigm shift in education brought on by pandemic crises. The impetus of this study is to listen to the voices of the stakeholders and points the phenomenological inquiry of the higher educational institutions on online experiences of faculty, administration and students. The indicators that need to focus are online teaching programs, self-learning direction and design are provided through online teaching problems. With this, students are encouraged to engage in self-directed learning using the resources and content of their classes, as well as provide online instructor transformation to provide information and data for motivation, engagement, interest, and effective lessons during the study process. The obstacles on educational curriculum may impede the learning capabilities of students and the quality and standard of learning is being sacrificed. Hence, the investigation of this paper’s findings, there is a great hindrance between the COVID-19 epidemic’s barriers and its impact on the educational system in Higher Education Institutions (HEIs). Therefore, HEIs may adapt blended learning and create learning modalities for future use.